Strength training for soccer - Swinnen, B. (Routledge, 2016)
Strength and power are key elements of soccer performance. A stronger player can sprint faster, jump higher, change direction more quickly and kick the ball harder. Strength Training for Soccer introduces the science of strength training for soccer. Working from a sound evidence-base, it explains how to develop a training routine that integrates the different components of soccer performance, including strength, speed, coordination and flexibility, and outlines modern periodization strategies that keep players closer to their peak over an extended period.